Rapid enzymatic assays for fecal contamination in aquatic environment: challenges, advances and prospects - Yuan, Xiaofei; Glidle, Andrew; Yang, Zhugen; Wang, Baojun (Elsevier, 2024)
Routine monitoring of sanitation and hygiene to identify fecal contamination in aquatic environments is an effective means to prevent threatening disease transmission. Compared to immunological or genetic methods performed in a central lab, enzymatic assays are considered simple, quick, cost-effective and thus promising for in-field (near) real-time detection. However, the long detection time for mildly polluted samples is a major obstacle to its deployment as an early warning system. Here, the challenges faced by the assays in real environmental sample measurements are summarized, followed by the current status of their field applications. Furthermore, the likelihood and ways are discussed for significant assay improvements using state-of-the-art synthetic biology technologies. Rapid advances in synthetic biology such as various new enabling tools for precise biomolecular manipulation and cell-free expression systems have great potential to address the present bottlenecks of the enzymatic assays, paving the way for better early warning strategies and performance.
Keywords: Rapid enzymatic assays; fecal contamination; E. coli; total coliform; synthetic biology; field application; aquatic environment; b-D-galactosidase